Low second to fourth digit ratio in Dupuytren disease. Issue 33 (August 2017) - Yokoi, Takuya; Uemura, Takuya; Kazuki, Kenichi; Onode, Ema; Shintani, Kosuke; Okada, Mitsuhiro; Nakamura, Hiroaki
Abstract : Abstract: The ratio of the lengths of the second and fourth digits (2D:4D) has been described as reflecting endogenous prenatal androgen exposure. In general, 2D:4D is lower in men than in women and has potential as a biomarker or predictor for various diseases, athletic ability, and academic performance. Dupuytren disease has digital flexion contractures and is known to predominate in men, but the pathogenesis of the disease remains unclear. To clarify the relationships between Dupuytren disease and endogenous androgens, we performed a retrospective analysis of hand radiographs to investigate 2D:4D in Dupuytren disease. The study included male patients with Dupuytren disease (n = 22) and a control group (n = 18) of male patients with carpal tunnel syndrome. Only unaffected hands, without contractures or osteoarthritis, were evaluated for the purpose of radiographic assessment. The lengths of the phalanx and metacarpal bones in the second and fourth digits were measured by 2 independent observers who each performed 2 sets of measurements separated by a minimum 1-week interval. The 2D:4D was calculated separately for the phalanges and metacarpals, and a combined (phalanx + metacarpal) 2D:4D was also calculated. The reliability of the observer measurements was established using the intraclass correlation coefficient, and both the intra- and interobserver reliability showed excellent agreement. We found that compared with control group, the Dupuytren disease group had significantly lower phalanx and combined 2D:4D. These findings suggest that endogenous prenatal androgens could contribute to the development of Dupuytren disease, leading to its characteristic clinical presentation predominantly in men and affecting the ulnar rays.